Post-Secondary Students' Purposes for Blogging - Leslie, Paul Henry; Murphy, Elizabeth (International Review of Research in Open and Distributed Learning, 2008)
The goal of the study was to explore post-secondary students’ purposes for blogging with particular attention to the social and instructional purposes. The sample of blogs came from an all-women’s college in the United Arab Emirates. Content analysis was conducted on eight blogs using previously tested instruments to identify social presence and knowledge construction. Authors of the blogs participated in a focus group discussion about the purposes for blogging. Findings revealed that the primary use of blogging was for social purposes. Self-disclosure was the most notable purpose for blogging, in addition to sharing emotional responses to learning. The lack of teaching presence may have influenced students’ use of blogging for social rather than instructional purposes.